(untitled) (Texas Journal of Medical Science, 2024)
Anthropometric studies of body mass index and spinal length in children were conducted and studied. Based on the results of the anthropometric examination, the differences in the results of the anthropometric examination of boys and girls aged 4-7 years living in rural and urban areas were analyzed. Based on these studies, the physical development of boys and girls aged 4–7 years living in urban areas was superior to the physical development of boys and girls aged 4–7 years living in rural areas.